Answers

2015-09-25T19:01:20+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let me assume the given data  as equation 1 and equation 2 :-

⇒ mx + ny = m ^{2} + n ^{2}  → Equation 1

x - y = 2n → Equation 2

→ Let us first multiply equation 2 by m to get anyone common term :-

→ We get as :- mx - my = 2 mn

Now let us do elimination method :-

→ Subtract equation 3 by 1, we get as :-

y(m-n) = (m-n) ^{2}  → y = m - n

⇒ Now substitute the value of y in equation 2 ....

x - ( m- n ) = 2n

x = m + n

Hence the value of x and y is :-

x =( m + n )

y = ( m-n )

----------------------------------------------------------------------------------


0